The Impact of Diet on Common Skin Disorders - Rezakovic, Saida; Pavlic, Mirjana; Navratil, Marta; Pocanic, Lidija; Žužul, Kristina; Kostovic, Krešimir (Journal of Nutritional Therapeutics, 2014)
The role of nutrition in the treatment of common dermatoses is often overlooked. Nevertheless, there is a large amount of evidence suggesting that diet may have an important role in the pathogenesis, as well as in determining the clinical course of common skin disorders; including acne, psoriasis, atopic dermatitis and allergic contact dermatitis. Consequently, diet could have significant preventive or therapeutic impact in these skin conditions. Psoriasis, atopic dermatitis and allergic contact dermatitis are chronic relapsing skin disorders characterised by remissions and flare-ups, requiring long-term maintenance therapy. Although acne occurs most commonly during adolescence, and rarely continues into adulthood, it has a large impact on patients' self-confidence and self-image. For each of these skin conditions, a variety of foods may lead to exacerbation of the disease and may have a significant role in increasing the risk of other comorbidities. The aim of this review is to present current knowledge on the relationship between high-fat and high glycemic index diet and acne and psoriasis. Additionally, possible role of nutritional supplementation in such will also be reviewed. And finally, the role of dietary restriction in patients with atopic dermatitis and low nickel diet, in those who are sensitive to nickel, will be discussed. Although future studies are necessary in order to evaluate the effect of diet in these skin disorders, identifying certain foods as a potential factor that could contribute to exacerbation of the disease or to development of further complications can provide important preventive measure.